Macrofungi Diversity in Wisdom Park UGM, Yogyakarta - Zahra, Safa Auli; Safitri, Salsabila; Nugraha, Farhan Satya; Hidayah, Hidayah; Aji, Oktira Roka (Universitas Ahmad Dahlan, 2023)
Indonesia's warm and humid tropical climate provides an ideal setting for the flourishing of fungi. Fungi are pivotal in the intricate balance of nutrient cycles and soil fertility within forest ecosystems. They can be broadly categorized into two types: microscopic fungi, which are minuscule and require observation under a microscope, and macroscopic fungi, which can be identified based on visible morphological features without additional tools. Forests, with their limited sunlight and high humidity due to the dense canopy of trees, serve as fertile grounds for a myriad of fungal species. This research aims to analyze fungal diversity using the exploratory survey method, involving direct search and observation of macrofungi. The sampling was conducted in May 2023 within the Wisdom Park UGM area, covering an area of 3,762.12 m² with coordinates 7° 46'09